Cardiac Autonomic Function and Psychological Characteristics of Heterosexual Female Perpetrators of Intimate Partner Physical Aggression - Brzozowski, Artur (Journal of interpersonal violence, 2021)
Intimate partner violence is predominantly viewed as a social problem of men’s violence against women. However, a growing evidence base suggests an equal prevalence rate for male and female perpetrated intimate partner physical aggression. Moreover, female perpetrated intimate partner violence is often assumed to be reactive, yet there is limited evidence to support this notion. In this article, we describe the results of two studies that investigated the prevalence of female perpetrated intimate partner physical aggression, and its correlates in heterosexual female university students. The relationships of personality traits, resting heart rate, and heart rate variability (a correlate of vagal activity) were compared between females who did and did not report having engaged in intimate partner physical aggression. In Study 1, we found that 30.9% of participants reported enacting intimate partner physical aggression during the preceding 12 months. This finding suggests that a considerable number of undergraduate females aggress against their intimate partners. Perpetrators, relative to nonperpetrators, scored higher on secondary psychopathic traits. In Study 2, female intimate partner violence was shown to be associated with low resting heart rate and high heart rate variability. Perpetrators, relative to nonperpetrators, scored higher on psychopathic traits that index emotional resilience and unempathic tendencies, and reported increased proactive and reactive aggression. This raises the possibility that some incidences of female intimate partner physical aggression represent proactive aggressive acts. These findings also support the frequently found association between low resting heart rate and aggression, but raise the prospect that the reported aggressive acts reflect high heart rate variability and strong parasympathetic nervous system activity.